Division-1 athletes` perceptions of sport specialization as a predictor of perfectionism - Hughes, J. N.; Jubenville, C. B.; Woltring, M. T.; Gray, H. J. (The Sport Journal, 2022)
Sport specialization is a trend amongst athletes today who are looking to gain an advantage over the competition. However, little research has examined the psychosocial consequences of this trend. One psychological construct that has not been sufficiently investigated regarding its relationship with sports specialization is perfectionism. Perfectionism is a multidimensional personality trait with two higher orders: perfectionistic strivings, and concerns; both of which are associated with adaptive and maladaptive outcomes in sport. Perfectionistic concerns have shown consistent negative associations with processes and outcomes. Perfectionistic strivings results have been inconsistent. The purpose of this study was to examine the previously unexplored relationship between specializing in sport and perfectionism concerns and strivings. Two multiple-hierarchical analyses were performed on a sample of 393 Division-1 NCAA student-athletes (M age = 20.21, SD 1.36) to investigate the level of sport specialization as a predictor of perfectionistic concerns and perfectionistic strivings. Findings indicated that student-athletes who are highly specialized were more likely to predict perfectionistic concerns, whereas moderate and low sport specializers did not have a relationship with perfectionistic concerns. Perfectionistic strivings had no significant relationship with sport specialization.